Characterization and performance evaluation of the XSPA‐500k detector using synchrotron radiation. (10th February 2021) - Nakaye, Yasukazu; Sakumura, Takuto; Sakuma, Yasutaka; Mikusu, Satoshi; Dawiec, Arkadiusz; Orsini, Fabienne; Grybos, Pawel; Szczygiel, Robert; Maj, Piotr; Ferrara, Joseph D.; Taguchi, Takeyoshi
Abstract : A Rigaku XSPA‐500k detector was evaluated and its performance characterized on the Metrology beamline at Synchrotron SOLEIL together by the SOLEIL Detector Group, AGH‐UST and Rigaku. Abstract : Hybrid photon counting (HPC) detectors are widely used at both synchrotron facilities and in‐house laboratories. The features of HPC detectors, such as no readout noise, high dynamic range, high frame rate, excellent point spread function, no blurring etc. along with fast data acquisition, provide a high‐performance detector with a low detection limit and high sensitivity. Several HPC detector systems have been developed around the world. A number of them are commercially available and used in academia and industry. One of the important features of an HPC detector is a fast readout speed. Most HPC detectors can easily achieve over 1000 frames s −1, one or two orders of magnitude faster than conventional CCD detectors. Nevertheless, advanced scientific challenges require ever faster detectors in order to study dynamical phenomena in matter. The XSPA‐500k detector can achieve 56 kframes s −1 continuously, without dead‐time between frames. Using `burst mode', a special mode of the UFXC32k ASIC, the frame rate reaches 1 000 000 frames s −1 . XSPA‐500k was fully evaluated at the Metrology beamline at Synchrotron SOLEIL (France) and its readout speed was confirmed by tracking the synchrotron bunch time structure. The uniformity of response, modulation transfer function, linearity, energy resolution and other performance metrics were also verified either with fluorescence X‐rays illuminating the full area of the detector or with the direct beam.